2018
DOI: 10.15419/bmrat.v5i11.498
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells accelerate liver regeneration in acute liver failure animal model

Abstract: Introduction: The massive hepatic necrosis of acute liver failure (ALF) results in a sudden loss of hepatic cells. Although most hepatocyte cells of ALF are completely lost, stem cell-derived circulating cells and endogenous progenitor cells rapidly regenerate them. Mesenchymal stem cells (MSCs) have a critical role in the regeneration of liver injury through regulating platelet-derived growth factor (PDGF) and vascular endothelial growth factor (VEGF) levels. However, their fluctuating levels in the healing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…The cells were rinsed in PBS and fixed with cold 70% ethanol (v/v) for 1 hour at room temperature, then rinsed three times with twice-distilled water. A volume of 1 mL 2% Alizarin Red solution (w/v) (pH 4.1-4.3) was added and the cells incubated for 30 minutes at a room temperature, then rinsed four times in twice-distilled water (Putra, et al, 2018).…”
Section: Mscs Differentiation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were rinsed in PBS and fixed with cold 70% ethanol (v/v) for 1 hour at room temperature, then rinsed three times with twice-distilled water. A volume of 1 mL 2% Alizarin Red solution (w/v) (pH 4.1-4.3) was added and the cells incubated for 30 minutes at a room temperature, then rinsed four times in twice-distilled water (Putra, et al, 2018).…”
Section: Mscs Differentiation Assaymentioning
confidence: 99%
“…Recently, some studies showed VEGF could stimulate vascular permeability, adhesion molecule expression, and granulation tissue formation to strengthen the healed wound (Johnson & Wilgus, 2014;Putra, et al, 2018). In regard to mediate a collagen synthesis, the VEGF used the PI3K/Akt pathway to activate fibroblast into myofibroblast (Lu, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic failure is a disastrous consequence of liver loss, in which the repair of residual hepatocytes is not performed in a timely and appropriate manner, resulting in increased mortality [103]. Massive hepatic necrosis in acute liver failure [97] is caused by sudden loss of hepatocytes due to a variety of acute injuries induced by hepatotoxic drugs, immune system attack, and viral infections [104][105][106]. While most hepatocytes are completely destroyed in ALF, the circulating Bone Marrow-derived cells and endogenous hepatocyte progenitor cells can rapidly regenerate the liver [107].…”
Section: Therapeutic Approaches For Acute Liver Failure and Pd-mscs Advmentioning
confidence: 99%
“…1. PD-MSCs are recruited to the damaged area by VCAM-1 and VLA-4 adhesion molecules [104,110,111] affecting the remaining hepatocytes through cell-cell contact and secretion of TGF-α, EGF, HGF, and VEGF tropic factors [112,113].…”
Section: Mechanisms Of Pd-msc Effect On Acute Liver Injurymentioning
confidence: 99%
See 1 more Smart Citation